CITRA LESBIAN DALAM NOVEL INDONESIA AWAL TAHUN 2000-AN KARYA PEREMPUAN PENGARANG - Kasnadi, Kasnadi (LITERA, 2017)
Abstract This study aims to describe lesbians' identity, interaction, struggle, and other figures' views of the existence of lesbian characters in Indonesian novels by female writers in the early 2000's. This was a qualitative descriptive study. The data were collected by the documentation technique using the reading-recording strategy. The data analysis used the content analysis technique. The results of the study are as follows. First, the identity of lesbian characters includes: (a) lesbians of "butch", "femme", and "andro" types; (b) lesbians of the "butch" type behaving like men; (c) lesbians of the "femme"type like women; and (d) lesbian of the "andro"type whocan be like men and women. Second, the interactions include: (a) the interaction of lesbian characters with fellow lesbians in an overt manner, and (b) the interaction of lesbian characters with family and society in a covert manner. Third, lesbian characters struggle to maintain their existence. Fourth, the views of other figures on the existence of lesbian characters are partly positive and partly negative. Keywords: lesbian images, feminism, Indonesian novels, female writers